Utilization of Broken Rice as a Fat Replacer in Low Calorie Tofu Salad Dressing - ธนสัมบัณณ์ พรทวี; พิชัยยงค์วงศ์ดี ผู้ช่วยศาสตราจารย์ ดร. สุวรรณา (Journal of Food Health and Bioenvironmental Science, 2017)
This research aims to produce a low calorie salad dressing from tofu and rice flour gel to replace yolks and vegetable oil. The most accepted basic recipe of salad dressing consisted of soft soy tofu 200 g, salad oil 235 g, rice vinegar 120 g, salt 7 g, sugar 114 g and black pepper powder 1.60 g. Then, 2 of types broken rice (Leuang pratew 123 and Thai jasmine 105) and wet or semi-milling processes were studied. The result showed that semi -milled Thai jasmine 105 gel was a suitable replacement for vegetable oil. This rice gel had a peak viscosity and water solubility index lower than that of wet milled flour. However, no difference of swelling power between both types of flour were found. It was found that the peak viscosity, final viscosity, setback and pasting temperature were 3255± 18.03, 3346±30.92, 1100±5.59 RUV and 82.83±0.19 ºC, respectively. Semi-milled flour was chosen because it had a lower production cost. In addition, reduced environmental problems, due to lower water usage in the production process, were found in semi-milled flour production. Replacing vegetable oil with 40% gel starch was optimal in the tofu salad dressing. The color of the product showed L*a*b* values of 51.87±0.28, 0.35±0.07 and 7.56 ±0.15, respectively. Viscosity of the product was 2,435±86.53 cPs. Chemical composition of the product showed moisture, protein, fat, fiber, ash and carbohydrate were 55.56±0.34, 6.28±0.03, 9.16±0.05, 1.41±0.10, 1.47±0.03 and 26.12±0.50 percent, respectively. Moreover, it complied to the standard of Thai community product for salad dressing. Substitution also decreased the level of total energy from 391.40 to 297.40 kcal and fat from 35.70 to 21.90 g. The experimental recipe had more protein, carbohydrate, fiber and mineral (sodium, calcium, phosphorus and iron) than the original tofu salad dressing. Consumers showed no significantly different preference between low calorie tofu salad dressing and the conventional full-fat dressing.